Islamic finance in Singapore: legal and regulatory challenges - Zul Kepli, Mohd Yazid (National University of Singapore, 2013)
Islamic finance has grown tremendously since its first revival in the 1970s. Strong support from Muslims and non-Muslims resulted in a market estimated to be around USD1.6 trillion. It is still growing at 15 percent to 20 percent per year, making it one of the fastest growing sectors in the finance industry globally. In recognition of the global trend, Singapore decided to make the best out of it. As Senior Minister Goh Chok Tong described it, “Singapore cannot be a complete international financial centre, if we do not offer Islamic financial services.” This article analyzes the characteristics of Islamic finance, the benefits and obstacles it brings, as well as its development and progress in Singapore. This article concludes with the challenges and possible solutions from the legal and regulatory aspects.